2015
DOI: 10.1103/physrevlett.114.147001
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of the Normal-State Pseudogap at a Lifshitz Transition in theBi2Sr2CaCu2O

Abstract: We report a fine tuned doping study of strongly overdoped Bi_{2}Sr_{2}CaCu_{2}O_{8+δ} single crystals using electronic Raman scattering. Combined with theoretical calculations, we show that the doping, at which the normal-state pseudogap closes, coincides with a Lifshitz quantum phase transition where the active holelike Fermi surface becomes electronlike. This conclusion suggests that the microscopic cause of the pseudogap is sensitive to the Fermi surface topology. Furthermore, we find that the superconducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 56 publications
18
86
0
Order By: Relevance
“…The T c , is also plotted. We first note that most of our data agree well with previous studies; gaps and transition temperatures from the present study follow the same trends with very little discrepancies 2,5,3136 . The only adjustment needed for the perfect overlap with the previous studies was the shift in the doping level p A .…”
Section: Resultssupporting
confidence: 92%
“…The T c , is also plotted. We first note that most of our data agree well with previous studies; gaps and transition temperatures from the present study follow the same trends with very little discrepancies 2,5,3136 . The only adjustment needed for the perfect overlap with the previous studies was the shift in the doping level p A .…”
Section: Resultssupporting
confidence: 92%
“…Preliminaries calculations advocate for this scenario but more deeper theoretical investigations are still required and will be developed in a near future. The Lifshitz transition in overdoped Bi-2212 has been first observed by ARPES in Bi-2212 [64] and recently detected by the analysis of the integrated Raman intensity as a function of doping level in Bi-2212 [65]. We found that p=0.22 is the starting point of the pseudogap as the doping decreases.…”
Section: Resultsmentioning
confidence: 66%
“…We suspect that at least the p=0.22 and 0.12 doping levels are directly connected to the doping evolution of the antinodal Bogoliubov quasiparticles spectral weight at low energy. p=0.22 corresponds to the doping level for which a Lifshitz transition occurs [64,65] and the antinodal quasiparticles spectral weight is strongly increased. On the other hand, p=0.12 corresponds to the doping level for which the charge ordering is well settled [71][72][73][74][75][76][77] and the antinodal quasiparticles spectral weight is strongly reduced.…”
Section: Resultsmentioning
confidence: 99%
“…The downward deviation below T * in BSCCO-2212 is ascribed to the reduction of inelastic scattering rate of electrons in the pseudo-gap phase, when temperature is lowered 30 . This characteristic T * may however be different 2 from the temperature of crossover into the pseudo-gap phase T pg , commonly detected by photo-emission, Raman, or tunneling spectroscopy 17, 31, 32 . It is well established in cuprates that in the Fermi liquid phase the upward deviation of R s ( T ) below T m follows the power law , where the exponent m is expected to increase with doping from 1 to 1.5–2 depending on the material 3, 4, 33 .…”
Section: Resultsmentioning
confidence: 94%
“…This value is indicative of the change introduced by doping and not an absolute measure of the carrier density since the electronic structure at the Fermi surface and its evolution with doping and temperature is complex and cannot be approximated by a single parabolic band. The Fermi surface evolves from hole-like to electron-like with doping and the contributions of these surfaces to the Hall coefficient are temperature dependent 1517 . To minimize errors related to this dependence, we consider R H values at the fixed, low temperature of 120 K 18, 19 for all doping values.…”
Section: Resultsmentioning
confidence: 99%